Separation of iron-nickel alloy nugget from limonitic laterite ore using self-reduction - Ju P.; Ryom K.; Hong K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
To efficiently extract nickel from low grade limonitic laterite ore, a separation method of iron-nickel alloy nugget by selfreduction of coal composite limonitic laterite ore briquette was investigated. In this investigation, in order to decrease the separation temperature of iron-nickel alloy nugget, the selective reduction by control of C/O ratio was introduced and reductant added in the briquette was inadequate for the reduction of nickel and iron. Nickel was preferentially reduced in the reduction process, while iron was partially reduced due to the lack of reductant. After reduction, a certain amount of FeO existed in the reduced product. This residual FeO had a great role in the formation of low melting point slag, which could promote the formation and the separation of iron-nickel alloy nugget at relatively low temperature. In this investigation, the reduction experiments were all conducted at 1300°C. To evaluate the formation and the separation of iron-nickel alloy nugget in the reduction process, we observed the patterns of reduced products under different C/O ratio, CaO addition ratio and holding time conditions. And then the effect of C/O ratio and CaO addition ratio on nickel content of nugget and nickel recovery ratio were investigated. The results showed that 0.7 of C/O ratio, 8% of CaO addition ratio and 40min of holding time were suitable for the separation of iron-nickel alloy nugget from limonitic laterite ore. Nickel and iron content of the nugget and the nickel recovery ratio were 4.75%, 89.51% and 85%, respectively. Nuggets were easily separated from slag by crushing and screening. This separation method could be applied to any limonitic laterite ore by adjusting C/O ratio and CaO addition ratio.